Pola Pemanfaatan Ruang pada Usaha Berbasis Rumah (UBR) di Klaster Batik Jenggot Kota Pekalongan - Arisngatiasih Arisngatiasih; Mohammad Muktiali (Jurnal Wilayah dan Lingkungan, 2015)
Housing has an important role in the economic development of the family. Besides has a function as a comfortable dwelling unit, the housing also used as a place to business activity through the Home Based Enterprises (HBE). Pekalongan City is the city where batik industries are growing rapidly. Cluster Batik Jenggot is the top three of batik clusters from 11 batik clusters in Pekalongan City. HBE is enterprises activities that highly contribute to the economic structure of Pekalongan City. However, HBE at Cluster Batik Jenggot is faced with the problems that the house used as a place of enterprises and dwelling has not clearly border. The aim of this research is to examine the pattern of utilization of space at HBE in Cluster Batik Jenggot. The study is conducted by qualitative research methods. Technique sampling is using snowball sampling to 9 respondents. The analysis is done by qualitative descriptive analysis. The results show that the pattern of space utilization at home for batik printing activities is classified into two typologies, i.e. mixture and separate typology. In the mixture typology, the utilization of space in the main building is both for a place to work and residence, which printing activity usually is done on the outside of the house. While in the separate typology, the working space is provided separately, which usually provided in the beside, behind, and in front of the main building. The utilization of spaces at UBR is adjusted to the type and timing of activity.